PELATIHAN KEPEMIMPINAN, SOFT SKILL DAN MENTAL HEALTH DI LEMBAGA KEMAHASISWAAN DI FAKULTAS ILMU ADMINISTRASI UNIVERSITAS BRAWIJAYA - Hairi, Muhammad Imam Akbar (PUAN INDONESIA, 2025)
The purpose of this training is to enhance leadership and soft skill also the importance of mental health for students in student organization in the faculty of administration, Brawijaya University. The soft skill training is consists of public speaking, entrepreneurship and sharing knowledge. Through leadership training, all the participants are enriched with the ability to be responsible personal and within the team or organization. In addition, soft skill training is enriched students with confidence to speak in public, insightful strategy in starting entrepreneurship, and tips and trick to be successful student and in developing career after graduation. Furthermore, mental health awareness is crucial for the student to avoid any mental disorder and help them to overcome mental burden during their study. The training is initiated in four student organizations: sport organization, master ceremony organization, choir organization and entrepreneurship organization. Due to multivariant in student organization background, the training is adjusted according to their needs. Overall, the training helped student in developing their personal and organization goals. Keywords – Leadership, Soft skill, Mental Health, Training, Student Organizations.